The Control of Exports – A Significant Factor of the Non-proliferation of Weapons of Mass Destruction (Czech Journal of International Relations, 2000)
Extensive changes have occurred during the past few years in the sphere of international security. The most prominent of these is the lesser likelihood of nuclear war between the super-powers and of a worldwide armed conflict, endangering human civilisation. But at the same time, the problem of the proliferation of weapons of mass destruction and the possibility of their utilization in local conflicts, representing a new threat to world peace and security, is coming to the forefront.The proliferation of nuclear, chemical and biological weapons and their carriers is regarded as a threat in the 21st century and requires the utmost and widest attention of world organisations and the pubic. Arms control, the control of exports and anti-proliferation measures are the major factors of the system of the struggle against proliferation. The authors of this essay deal in great detail with the control of exports as one of the key elements of a comprehensive non-proliferation strategy. They analyze the system of export control and its fundamental elements, international treaties banning the proliferation of weapons of mass destruction as well as control regimes of multilateral export controls. The Czech Republic takes an active part in this process since it participates in the activities of international control associations, involved in the sphere of the non-proliferation of conventional arms and weapons of mass destruction.The further improvement of export control from the point of view of current non-proliferation which is characterized mainly by global integration and rapid technological progress, lies in increasing the effectiveness of national export control systems and in international cooperation in creating a global export central system.